Frontispiece: RhIII‐Catalyzed Functionalization of closo‐Dodecaborates by Selective B−H Activation: Bypassing Competitive C−H Activation. Issue 59 (23rd October 2018) - Zhang, Yuanbin; Wang, Tao; Wang, Lingyao; Sun, Yuji; Lin, Furong; Liu, Jiyong; Duttwyler, Simon
Abstract : The closo‐dodecaborate cage is a fundamental icosahedral boron cluster, and the selective modification of the cage positions has been a major challenge. A Rh‐catalyzed B–H functionalization–cyclization cascade of closo ‐dodecaborate amides is described which proceeds chemoselectively in the presence of C–H bonds prone to competitive activation. The Frontispiece picture shows the formation of structurally intriguing products. For more information, see the Full Paper by S. Duttwyler et al. on page 15812 ff.